Implementasi Pendekatan Deep Learning dalam Pembelajaran Bahasa Indonesia - Suar Adnyana, I Ketut (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2024)
This study is a qualitative descriptive study. The aim of this study is to find learning methods in Indonesian language subjects by applying a deep learning approach. The method used in this study is the literature study method with the steps 1) identifying literature sources 2) selecting relevant literature, and 3) analyzing the literature. From the results of the study it can be determined that the methods that can be applied in learning Indonesian are problem-based learning methods, project-based learning, inquiry, and flipped classroom.